Penggunaan Kontrasepsi Hormonal dan Produksi Air Susu Ibu di Puskesmas Poasia - La Ode Alifariki; Adius Kusnan; Ida Mardhiah Afrini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Breast milk is the best natural nutrient for babies because it contains energy needs and substances needed during the first six months of a baby's life. If during lactation the mother uses hormonal contraception, the lactation hormone namely the hormone prolactin and oxytocin will be suppressed so that the process of egg maturation immediately occurs, the mother immediately enters the fertile period and the milk production is disrupted. The purpose of this study was to determine the relationship between hormonal contraception and breast milk production in nursing mothers at Poasia Community Health Center, Kendari City in 2019. This type of research was analytic descriptive using a cross sectional approach. The population in this study was all mothers who breastfeeded at the Poasia Community Health Center in Kendari City in October to November as many as 70 with a sample of 41 respondents. The statistical test used was Chi square at α = 0.05. The results showed that most were using 3 types of 3-month injectable hormonal contraceptives (46.3%), following the type of mini pills as many as 9 people (22.0%), implants as many as 6 people (14.6%), injecting 1 month as many as 5 people (12.2%) and the least is using a combination pill of 2 people (4.9%). The production of breast milk was 27 people (65.9%) and the current category was 14 people (34.1%). Statistical test results indicate that there was a relationship between the use of hormonal contraceptives and breast milk production in the work area of Poasia Community Health Center, Kendari City in 2019, with a p value of 0.004